The Current Situation and Trend of the Labor Force of Mining Sector in Mongolia - Altanchimeg Zanabazar; Myagmarsuren Ukhnaa; Huo Xuexi; Shurentsetseg Bira; Sarantuya Jigjiddorj; Odgerel Pagvajav (SCAD Independent, 2017)
The mining was declared as a priority sector within the framework of the government policy to support the export industries. In the past years, the mining extraction increased steady and growth showed an increase of 8.3 percent in 2012 compared to the previous year, 19.4 percent in 2013 and 24.4 percent in 2014 respectively. In the current stage when the mining sector production plays a crucial role in the accumulation of the state budget, one of the key issues of improving the benefits of this sector is the impact of the labor force. By the labor market survey of 2013 out of 219013 job offers 14541 jobs or 6.6 percent were in the mining exploration sectors. Due to the mining sector booming, the job opportunities have increased and there is a need for the government policy and regulations for the education policies, curriculum modifications of the universities, colleges and vocation training as well as labor migration. According to the results of the study, the major challenge for the mining sector is lack of creative, enthusiastic and professional personnel. Therefore, identification of the accurate government policies that would ensure the balance between supply, the demand for the human resources in the mining sector and cohesion of the stakeholders are becoming essential.